Treatment of dyslipidemia - Tonkin, Andrew (Faculty of 1000 Ltd, 2014)
Atherosclerotic cardiovascular disease (including coronary heart disease, stroke and peripheral arterial disease) is the leading cause of death globally. Abnormal blood lipids (dyslipidemia), smoking, and high blood pressure are responsible for more than 75% of cases. Aggressive low-density lipoprotein (LDL)-cholesterol lowering therapy, particularly statins, appear to be the most effective of the therapeutic approaches, but even with their use, cardiovascular disease event rates remain relatively high, underpinning the quest for novel treatments. In this review we discuss recent advances in the field and what remains to be done to reduce this rate further. In particular, in addition to development and investigation of new LDL-cholesterol lowering therapies, there has been a major focus on treatments to favorably influence high-density lipoprotein (HDL)-cholesterol and triglyceride concentrations. However, to this time, approaches to the latter have been somewhat disappointing, but they may have particular benefits in people with diabetes. As atherosclerosis is a largely preventable process, which is driven particularly by behavioral and lifestyle factors, attention to other modifiable risk factors is imperative.